2020
DOI: 10.1155/2020/4980609
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Perituberal Tissue in Epileptic Patients with Tuberous Sclerosis Complex by the Transcriptome Analysis

Abstract: Epilepsy is most common in patients with tuberous sclerosis complex (TSC). However, in addition to the challenging treatment, the pathogenesis of epilepsy is still controversial. To determine the transcriptome characteristics of perituberal tissue (PT) and clarify its role in the pathogenesis of epilepsy, GSE16969 was downloaded from the GEO database for further study by comprehensive bioinformatics analysis. Identification of differentially expressed genes (DEGs), functional enrichment analysis, construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…ANXA2, an important annex in family member, was reported to be highly expressed in patients with tuberous sclerosis with seizures. However, it has not been studied in epilepsy 18,38 . Given that synaptic dysfunction is closely associated with epilepsy and that previous reports indicate that ANXA2 plays a major role in the development of excitatory synaptic activity, we speculate that ANXA2 can participate in epileptogenesis by regulating synaptic transmission.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…ANXA2, an important annex in family member, was reported to be highly expressed in patients with tuberous sclerosis with seizures. However, it has not been studied in epilepsy 18,38 . Given that synaptic dysfunction is closely associated with epilepsy and that previous reports indicate that ANXA2 plays a major role in the development of excitatory synaptic activity, we speculate that ANXA2 can participate in epileptogenesis by regulating synaptic transmission.…”
Section: Discussionmentioning
confidence: 86%
“…However, it has not been studied in epilepsy. 18,38 Given AMPAR surface proteins, including GluA1, are dynamically changing; their distribution is tightly regulated, and AMPAR modification is largely dependent on serine phosphorylation of GluA1. 39 Using an immunoprecipitation assay, we found that ANXA2interacts with GluA1 in epileptic hippocampal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further confirm our results, GFAP and CD44 were selected for validation in tissue sections using immunofluorescence, which showed a consistent trend with proteomics results. These proteins were chosen because blood GFAP is an FDA authorized marker in individuals with suspected TBI [ 23 ] and both the proteins have distinguished roles in synaptic plasticity and neurogenesis, with reported associations in Parkinson’s and dementia [ 24 29 ]. CD44 was found to be upregulated in 7 days post-TBI compared to 1 day post-TBI and Sham in all sub-regions except SM where it showed upregulation in both the TBI time points as compared to Sham.…”
Section: Resultsmentioning
confidence: 99%